Pengaruh Penanaman Modal Dalam Negeri, Penanaman Modal Asing dan Utang Luar Negeri Terhadap Pertumbuhan Ekonomi Indonesia - Sari, Indah Puspita; Kamal, Safwan; Amin, Muhammad; Astina, Chahayu (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2024)
Purpose – This research aims to determine and analyze the influence of domestic investment, foreign investment and foreign debt on Indonesia's economic growth. The data used is secondary data obtained from BPS in the form of PMDN, PMA, Foreign Debt and Indonesian GDP data for 2011-2022. Method – The research method used is a qualitative approach with data analysis method uses multiple linear regression analysis. Results – From the results of data analysis, it is known that PMDN has a positive effect of 0.133 on Indonesia's economic growth as evidenced by the sig value. 0.022 < 0.05. This shows that the higher the PMDN and its targeted use, especially in the productive sector, the more Indonesia's economic growth will increase. PMA has a positive effect of 0.265 on Indonesia's economic growth as evidenced by the sig value. 0.012 < 0.05. This shows that the higher the FDI and its targeted use, especially in the productive sector, the more Indonesia's economic growth will increase. Foreign debt has a positive effect of 0.048 on Indonesia's economic growth as evidenced by the sig value. 0.028 < 0.05. In this case, foreign debt is used to finance development in Indonesia, especially strategic projects in Indonesia in the fields of industry, transportation and other strategic projects. PMDN, PMA and foreign debt simultaneously have a positive and significant effect on Indonesia's economic growth as evidenced by the sig value. 0.015 < 0.05. This shows that the higher the PMDN and PMA and their use is right on target, especially in the productive sector, the more Indonesia's economic growth will increase. On the other hand, foreign debt is used to finance development in Indonesia, especially strategic projects in Indonesia in the fields of industry, transportation and other strategic projects.